Accuracy of the Haigis and SRK/T Formulas in Eyes Longer than 29.0 mm and the Influence of Central Corneal Keratometry Reading. (2nd November 2018) - Zhang, Zhihua; Miao, Yuyu; Fang, Xiaoling; Luo, Qin; Wang, Yulan
ABSTRACT: Purpose : To examine the potential relationship of central corneal keratometry reading (K value) to intraocular lens (IOL) power calculation in extremely long eyes. Materials and methods : Sixty-three consecutive eyes with an axial length (AL) longer than 29.0 mm were prospectively enrolled at Shanghai General Hospital. All eyes underwent uneventful cataract surgery. Central corneal keratometry, anterior chamber depth, and AL were measured, and IOL power was calculated using the Haigis and SRK/T formulas. The refractive error associated with both formulas was calculated, and its relationship with associated factors was also analyzed. Results : Linear regression showed a statistically significant relationship between prediction error and K value with both Haigis and SRK/T (P < 0.001, R 2  = 0.343 and P < 0.001, R 2  = 0.225, respectively). In general, a higher K value was associated with a hyperopic outcome, whereas a lower K value was associated with a myopic outcome. There was no difference in the median absolute error (MedAE) when comparing Haigis and SRK/T (P = 0.081). The 63 eyes were subsequently divided into an L group (K value < 44.02) and an H group (K value > 44.02) according to the K value. The MedAE produced by SRK/T was lower than that produced by Haigis in group L, while the MedAE produced by SRK/T was similar to that produced by Haigis in group H (P = 0.020 and P = 0.799, respectively). Conclusions : The average keratometry reading significantly correlated with the prediction error using Haigis and SRK/T. An adjustment of formulas according to the K value could achieve better outcomes in long eyes.